(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study investigates the efficiency of the tapioca value chain at the Bogor Cassava Center (BCC) Cooperative by applying a combined Data Envelopment Analysis–Slack Based Model (DEA–SBM) and Stochastic Frontier Analysis (SFA) framework. The integration of stage-wise DEA and network efficiency models with SFA enables a robust assessment of technical efficiency, inefficiency determinants, and stage-specific performance along the cassava-to-tapioca chain. Using primary data from 30 cooperative members across two production stages—cassava cultivation and tapioca processing–distribution—the results reveal heterogeneous efficiency patterns, with average DEA–SBM efficiency scores ranging from 0.62 to 0.81 and SFA technical efficiency levels from 0.58 to 0.77. Key determinants of inefficiency include labor quality, capital intensity, and market access, underscoring the need for targeted interventions in resource allocation and governance. Furthermore, the study introduces Blockchain Value Transparency (BVT) as a novel governance mechanism to mitigate inefficiencies related to information asymmetry, traceability gaps, and unfair pricing. By linking efficiency diagnostics with blockchain-based smart contracts and transparent price ledgers, the paper highlights managerial implications to strengthen trust, enable fair value distribution, and accelerate competitiveness in Indonesia’s tapioca sector. These findings contribute to the literature on agri-food value chain efficiency and provide actionable policy insights for cooperative-based agribusiness models in Southeast Asia.